2002
DOI: 10.1073/pnas.0235349100
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis drives cell-cycle transitions in Xenopus laevis egg extracts

Abstract: Cells progressing through the cell cycle must commit irreversibly to mitosis without slipping back to interphase before properly segregating their chromosomes. A mathematical model of cell-cycle progression in cell-free egg extracts from frog predicts that irreversible transitions into and out of mitosis are driven by hysteresis in the molecular control system. Hysteresis refers to toggle-like switching behavior in a dynamical system. In the mathematical model, the toggle switch is created by positive feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
446
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 462 publications
(484 citation statements)
references
References 38 publications
34
446
0
4
Order By: Relevance
“…For the Marlovits parameter set, Table 1, T i = 8 nM and T a = 17 nM. The theoretical prediction of two distinct thresholds was confirmed experimentally (8,9). B) MPF oscillations are faster and smaller if Cdk1 is not phosphorylatable by Wee1.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…For the Marlovits parameter set, Table 1, T i = 8 nM and T a = 17 nM. The theoretical prediction of two distinct thresholds was confirmed experimentally (8,9). B) MPF oscillations are faster and smaller if Cdk1 is not phosphorylatable by Wee1.…”
Section: Discussionmentioning
confidence: 67%
“…This prediction was first made by Novak and Tyson in 1993. Although no published studies showed evidence of this "critical slowing down," subsequent experiments confirmed this prediction (8). This example illustrates that mathematical models of the cell cycle can both be informed by and can inform experimental studies.…”
Section: Running Simulations Of the Modelmentioning
confidence: 86%
See 2 more Smart Citations
“…En présence de la rétroaction négative due à l'induction par la cdc2 de la dégradation de la cycline, une telle bistabilité conduit à des oscillations entretenues sous la forme d'un cycle d'hystérèse décrit de manière répétitive. Ces prédictions théoriques ont été vérifiées expérimentalement sur des oeufs de grenouille [27,28].…”
Section: Un Oscillateur Mitotique Dans Les Cellules Embryonnaires De unclassified